Gut Guardianship: Recommendations for Rational Use of Proton Pump Inhibitors in Chronic Kidney Disease - Sourabh Sharma; Pawan Rawal; Sanjay Kalra (Journal of the Pakistan Medical Association, 2025)
The widespread use of proton pump inhibitors (PPIs) has raised safety concerns, especially among patients with chronic kidney disease (CKD), where long-term use has been linked with acute interstitial nephritis (AIN), hypomagnesaemia, and potential progression to endstage kidney disease (ESKD). Recent observational studies and meta-analyses have yielded mixed evidence, calling for a nuanced and individualized approach to acid suppression in CKD. The concept of gut guardianship emphasizes cautious, indication-based prescribing, dose minimization, and structured deprescribing to preserve gut–renal health. This article reviews the current evidence and proposes a clinical toolkit for rational PPI use in CKD, based on risk stratification, guideline-based indications, and ongoing monitoring. Keywords: Acid suppression, Chronic kidney disease, Gut microbiome, Nephrotoxicity, Proton pump inhibitors